Composite additive as well as preparation method and application thereof

By adding composite additives to high-temperature heat-treated oil, the occurrence of chain reaction is suppressed, and the product quality problems caused by viscosity attenuation of high-temperature heat-treated oil are solved, which significantly improves the thermal stability of the oil and the consistency of product quality.

CN119709302APending Publication Date: 2025-03-28NANJING KERUN LUBRICANTS +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411966003.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Product quality problems caused by viscosity attenuation after long-term use of high-temperature heat-treated oil, including the decrease in oil viscosity, decrease in flash point and oil flue gas generation, which affects the quality of metal heat treatment.

Method used

A composite additive is adopted, and the composition includes sodium petroleum sulfonate, tetrahydronaphthalene, benzyl alcohol, o-hydroxybenzyl alcohol, tetrahydronaphthalene and 2,6-di-tert-butyl p-methylphenol. By adding the composite additive to the heat-treated oil, the occurrence of chain reaction is inhibited, thereby improving the thermal stability of the heat-treated oil.

Benefits of technology

It effectively improves the viscosity stability of high-temperature heat-treated oil, avoids the viscosity drop and the generation of surface filamentous contaminants, and improves the consistency of product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709302A_ABST
    Figure CN119709302A_ABST
Patent Text Reader

Abstract

The invention discloses a composite additive which is prepared from the following components in parts by weight: 15 to 20 parts of petroleum sodium sulfonate, 65 to 75 parts of tetrahydronaphthalene, 3 to 5 parts of benzyl alcohol, 2.5 to 4 parts of o-hydroxybenzyl alcohol, 3.5 to 4 parts of tetrahydronaphthol and 1 to 2 parts of 2, 6-di-tert-butyl-p-methylphenol. The invention further discloses a preparation method of the composite additive and application of the composite additive in high-temperature heat treatment oil. The composite additive can effectively improve the viscosity attenuation problem in the use process of the high-temperature heat treatment oil, so that the stability of the heat treatment oil is effectively improved, and meanwhile, the problems of generation of filamentous pollutants on the surface caused by viscosity attenuation and product quality caused by viscosity attenuation can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite additive, and also relates to a preparation method of the composite additive and application of the composite additive in high-temperature heat treatment oil. Background Art

[0002] Metal heat treatment is one of the important processes in mechanical manufacturing. Metal heat treatment is a process method in which a metal workpiece is placed in a certain heat treatment medium and heated to an appropriate temperature, and then kept at this temperature for a certain period of time, and then cooled at different rates. Metal heat treatment generally does not change the shape of the workpiece and the chemical composition of the overall material, but by changing the microstructure of the workpiece material, or changing the chemical composition of the workpiece surface material, it imparts or improves the mechanical, physical and chemical properties of the workpiece material, thereby improving the strength and hardness of the metal material or improving its toughness so that the workpiece obtains different performance. Metal heat treatment will implement heat treatment processes such as quenching, tempering, annealing and normalizing. Among them, quenching is to place the heated metal material (above 850°C) in a specific cooling medium to cause it to undergo a phase change and transform into a specific quenching structure. Mineral oil and its composition are widely used in quenching cooling media, so mineral oil-based base oil is an important component of quenching oil. Mineral oil-based base oil refers to a mixture of hydrocarbons extracted from petroleum. From the perspective of molecular structure, base oil contains a large amount of long carbon chain straight chain or branched chain alkanes, as well as a small amount of cycloalkanes and aromatics. Its structure is shown below:

[0003]

[0004] Since heat treatment quenching oil needs to cool a large number of high-temperature red-hot workpieces (temperature above about 850℃) to room temperature in a short time, a large amount of heat needs to rely on base oil for heat transfer. In this process, various hydrocarbon molecules in the base oil are subjected to high temperature, thermal cracking reactions will occur, CC bonds in their molecular structure will break, and macromolecular compounds will gradually transform into small molecular compounds. Due to the need to serve in a high-temperature environment for a long time, quenching oil products will undergo serious changes with the increase of service time. Macroscopically, the viscosity of the oil products decreases, the flash point decreases, and a large amount of oil fume is generated. In particular, the change in viscosity will have a serious impact on the quality of metals after heat treatment, and may cause a large number of quenched workpieces to be reworked or scrapped. At the same time, after long-term use of high-temperature heat treatment oil, its high-temperature cracking products will continue to accumulate and accumulate, and it is very easy to deposit on the surface of the workpiece, reducing the appearance of the heat-treated workpiece. Clean, in serious cases, affecting the local organizational structure and hardness. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a composite additive, which can effectively improve the viscosity attenuation problem of the high-temperature heat treatment oil during use by adding the composite additive to the high-temperature heat treatment oil, thereby effectively solving the product quality problem of the existing high-temperature heat treatment oil caused by viscosity attenuation; another purpose of the present invention is to provide a preparation method of the above-mentioned composite additive and its application in high-temperature heat treatment oil.

[0006] Technical solution: The composite additive of the present invention is prepared from the following components in parts by weight: 15-20 parts of sodium petroleum sulfonate, 65-75 parts of tetralin, 3-5 parts of benzyl alcohol, 2.5-4 parts of o-hydroxybenzyl alcohol, 3.5-4 parts of tetralin and 1-2 parts of 2,6-di-tert-butyl-p-methylphenol.

[0007] Wherein, the sodium petroleum sulfonate is any one of synthetic sodium petroleum sulfonate and natural sodium petroleum sulfonate.

[0008] The preparation method of the composite additive is specifically as follows: sodium petroleum sulfonate, tetralin, benzyl alcohol, o-hydroxybenzyl alcohol, tetralinol and 2,6-di-tert-butyl-p-methylphenol are mixed in a formulated amount, reacted at high temperature in an inert atmosphere, and cooled to room temperature after the reaction to obtain the composite additive.

[0009] The reaction temperature is 85-95°C and the reaction time is 2-3.5h.

[0010] During the reaction, the stirring speed is 20 to 35 rpm.

[0011] Application of the above composite additive in high temperature heat treatment oil.

[0012] The amount of the composite additive added to the high-temperature heat treatment oil is 8-10% of the mass of the high-temperature heat treatment oil.

[0013] The principle of the present invention is: by adding a composite additive to the heat treatment oil, the composite additive can inhibit the occurrence of chain reactions from the source of the cracking mechanism to improve the thermal stability of the heat treatment oil, thereby improving the viscosity stability of the oil. Specifically, the composite additive of the present invention can quickly generate hydrogen free radicals under high temperature, and a large number of hydrogen free radicals can reduce the free radicals generated by the cracking of hydrocarbons in the heat treatment oil, improve the formation of saturated products, and thus play a role in improving the thermal stability of the heat treatment oil; that is, when the hydrocarbon molecules in the quenching oil encounter high temperature, molecular chain breakage will occur to generate free radicals. The composite additive of the present invention can release hydrogen free radicals to the hydrocarbon molecules in the initial stage of chain breaking to form saturated and stable hydrocarbon molecules, thereby reducing the concentration of free radicals in the initial stage of the chain reaction, so as to achieve the effect of reducing the free radicals brought by the chain transfer stage from continuously attacking the hydrocarbon molecules and causing further decomposition; the composite additive of the present invention inhibits the occurrence of chain reactions from the source of cracking, thereby reducing the occurrence of free radical coking caused by thermal cracking, and alleviating the viscosity drop caused by thermal cracking, thereby improving the stability of the heat treatment oil.

[0014] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the composite additive of the present invention can effectively improve the viscosity decay problem of high-temperature heat treatment oil during use, thereby effectively improving the stability of the heat treatment oil, and at the same time can solve the generation of surface filamentous pollutants caused by viscosity decay and product quality problems caused by viscosity decay. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a photo of the appearance of the workpiece corresponding to the brightness test of Example 1;

[0016] Figure 2 This is a photo of the appearance of the workpiece corresponding to the brightness test of Example 2;

[0017] Figure 3 This is a photo of the appearance of the workpiece corresponding to the brightness test of Comparative Example 1;

[0018] Figure 4 This is a photo of the appearance of the workpiece corresponding to the brightness test of Comparative Example 2;

[0019] Figure 5 This is a photo of the appearance of the workpiece corresponding to the brightness test of Comparative Example 3;

[0020] Figure 6 This is a photo of the appearance of the corresponding workpiece when the No. 1 isothermal (graded) quenching oil obtained in Example 1 with an addition amount of 3wt.% was tested for brightness;

[0021] Figure 7 This is a photo of the appearance of the corresponding workpiece when the No. 1 isothermal (graded) quenching oil obtained in Example 1 with an addition amount of 5wt.% was tested for brightness;

[0022] Figure 8 This is a photo of the appearance of the corresponding workpiece when the No. 1 isothermal (graded) quenching oil obtained in Example 1 with an addition amount of 8wt.% was tested for brightness;

[0023] Fig. 9 This is a photo of the appearance of the corresponding workpiece when the No. 1 isothermal (graded) quenching oil obtained in Example 1 with an addition amount of 10wt.% was tested for brightness;

[0024] Fig.10 This is a photograph of the appearance of the corresponding workpiece when the No. 1 isothermal (graded) quenching oil without the composite additive of Example 1 was tested for brightness. DETAILED DESCRIPTION

[0025] Example 1

[0026] The composite additive of the present invention is prepared by the following method, specifically: in a 500mL flask with an electric stirrer and a condenser, 15 parts of medium molecular weight petroleum sodium sulfonate (medium molecular weight is usually 300-500) (7 parts of synthetic petroleum sodium sulfonate, 8 parts of natural petroleum sodium sulfonate), 75 parts of tetralin, 3 parts of benzyl alcohol, 2.5 parts of o-hydroxybenzyl alcohol, 3.5 parts of tetralinol and 1 part of 2,6-di-tert-butyl-p-methylphenol are added; nitrogen is introduced, stirring is started (stirring speed is 35rpm), heating temperature is set to 85°C, and reaction is continued for 3.5 hours; after the reaction is completed, the system is cooled, and the composite additive is obtained after filtering.

[0027] Example 2

[0028] The composite additive of the present invention is prepared by the following method, specifically: in a 500mL flask with an electric stirrer and a condenser, 20 parts of natural petroleum sodium sulfonate with a medium molecular weight, 65 parts of tetralin, 5 parts of benzyl alcohol, 4 parts of o-hydroxybenzyl alcohol, 4 parts of tetralin and 2 parts of 2,6-di-tert-butyl-p-methylphenol are added; nitrogen is introduced, stirring is started (stirring speed is 35rpm), heating temperature is set to 95°C, and reaction is continued for 2 hours; after the reaction is completed, the system is cooled, and the composite additive is obtained after filtering.

[0029] Comparative Example 1

[0030] A composite additive is prepared by the following method, specifically: in a 500 mL flask with an electric stirrer and a condenser, 5 parts of synthetic petroleum sodium sulfonate with a medium molecular weight, 65 parts of tetralin, 18 parts of benzyl alcohol, 5 parts of o-hydroxybenzyl alcohol, 5 parts of tetralinol and 2 parts of 2,6-di-tert-butyl-p-methylphenol are added; nitrogen is introduced, stirring is started (stirring speed is 35 rpm), the heating temperature is set to 85°C, and the reaction is continued for 3.5 hours; after the reaction is completed, the system is cooled, and the composite additive is obtained after filtering.

[0031] Comparative Example 2

[0032] A composite additive is prepared by the following method, specifically: in a 500 mL flask with an electric stirrer and a condenser, 4 parts of synthetic petroleum sodium sulfonate with a medium molecular weight, 3 parts of natural petroleum sodium sulfonate, 65 parts of tetralin, 5 parts of benzyl alcohol, 4 parts of o-hydroxybenzyl alcohol, 17 parts of tetralinol and 2 parts of 2,6-di-tert-butyl-p-methylphenol are added; nitrogen is introduced, stirring is started (stirring speed is 35 rpm), the heating temperature is set to 85°C, and the reaction is continued for 3.5 hours; after the reaction is completed, the system is cooled, and the composite additive is obtained after filtering.

[0033] Comparative Example 3

[0034] A composite additive is prepared by the following method, specifically: in a 500 mL flask with an electric stirrer and a condenser, 6 parts of synthetic petroleum sodium sulfonate with a medium molecular weight, 65 parts of tetralin, 5 parts of benzyl alcohol, 18 parts of o-hydroxybenzyl alcohol, 4 parts of tetralin and 2 parts of 2,6-di-tert-butyl-p-methylphenol are added; nitrogen is introduced, stirring is started (stirring speed is 35 rpm), the heating temperature is set to 85°C, and the reaction is continued for 3.5 hours; after the reaction is completed, the system is cooled, and the composite additive is obtained after filtering.

[0035] The composite additives of Examples 1 to 2 and Comparative Examples 1 to 3 were respectively added to isothermal (graded) quenching oil No. 1, and the added amount of each composite additive was 10% of isothermal (graded) quenching oil No. 1, that is, 80g of the composite additive was added to 720g of quenching oil; after stirring evenly, heat-treated isothermal (graded) quenching oil No. 1-A1 was obtained.

[0036] Characterization of the properties of the heat-treated No. 1 isothermal (graded) quenching oil-A1 obtained in Examples 1 to 2 and Comparative Examples 1 to 3

[0037]

[0038] Note: 1. Test standard: ASTM D7279-16 Standard Test Method for KinematicViscosity of Transparent and Opaque Liquids by Automated Houillon Viscometer.

[0039] 2. The detection method is: according to the method disclosed in Chinese patent CN212301382U, the sample is placed in a testing machine for cyclic quenching 1000 times, and the viscosity change rate of the sample before and after quenching is tested. The viscosity change rate = (viscosity after quenching 1000 times - viscosity after quenching 0 times) / viscosity after quenching 0 times * 100%.

[0040] 3. Testing standard: GB / T 3536 Determination of flash point and fire point of petroleum products - Cleveland open cup method.

[0041] 4. Testing standard: SH / T 0564 heat treatment oil.

[0042] The method used for the brightness grade test is the method specified in Appendix A of SH / T 0564. This standard is currently the only publicly available brightness grade test method in China. The standard does not specify the oil temperature of the quenching oil to be tested. The default is to test at room temperature. However, the standard stipulates that the insulation temperature of the quenched workpiece is 840℃±5℃, and the temperature is kept constant for 5 minutes to ensure that the workpiece temperature is stable in the range of 840±5℃. At this temperature, the workpiece enters the quenching oil for quenching test. After the quenching is completed, the oil temperature is cooled to room temperature, the workpiece is taken out, cleaned with industrial solvent oil, wiped dry with silk cloth, and the appearance brightness of the workpiece surface is observed. The standard does not specify the use time of the oil. In this experiment, in order to verify the ability of the additive to improve the brightness of the quenching oil, the sample used is the brightness test of the quenching oil after 1000 cycles of quenching.

[0043] It can be seen from Table 1 that, under the same addition ratio, the present invention has a more excellent viscosity stability control capability for No. 1 isothermal (graded) quenching oil, and can maintain the brightness of the quenching oil after multiple quenching in an optimal state.

[0044] The composite additive of Example 1 was added into the No. 1 isothermal (graded) quenching oil in different amounts, and after uniform stirring, heat-treated No. 1 isothermal (graded) quenching oil-A2 with addition amounts of 3%, 5%, 8% and 10% were obtained respectively.

[0045] Characterization of the properties of heat treatment No. 1 isothermal (graded) quenching oil-A2 obtained based on different addition amounts in Example 1

[0046]

[0047] The composite additive of the present invention can effectively improve the viscosity stability of the heat treatment oil, thereby improving the appearance of the workpiece after the heat treatment, obtaining a smooth surface, and further effectively improving the consistency of product quality.

Claims

1. A composite additive, characterized in that: The invention is prepared from the following components in parts by weight: 15-20 parts of sodium petroleum sulfonate, 65-75 parts of tetralin, 3-5 parts of benzyl alcohol, 2.5-4 parts of o-hydroxybenzyl alcohol, 3.5-4 parts of tetralin and 1-2 parts of 2,6-di-tert-butyl-p-methylphenol.

2. The composite additive according to claim 1, characterized in that: The sodium petroleum sulfonate is any one of synthetic sodium petroleum sulfonate and natural sodium petroleum sulfonate.

3. The method for preparing the composite additive according to claim 1, characterized in that: Specifically, sodium petroleum sulfonate, tetralin, benzyl alcohol, o-hydroxybenzyl alcohol, tetralinol and 2,6-di-tert-butyl-p-methylphenol are mixed in a formula amount, reacted at high temperature in an inert atmosphere, and cooled to room temperature after the reaction to obtain a composite additive.

4. The preparation method according to claim 3, characterized in that: The reaction temperature is 85-95°C, and the reaction time is 2-3.5h.

5. The preparation method according to claim 3, characterized in that: During the reaction, the stirring speed was 20-35 rpm.

6. Use of the composite additive according to claim 1 in high-temperature heat treatment oil.

7. The use according to claim 6, characterized in that: The amount of the composite additive added to the high-temperature heat treatment oil is not less than 5% of the mass of the high-temperature heat treatment oil.

8. The use according to claim 7, characterized in that: The amount of the composite additive added to the high-temperature heat treatment oil is 8 to 10% of the mass of the high-temperature heat treatment oil.

Citation Information

Patent Citations

  • Device for testing thermal stability of quenching medium

    CN212301382U